Simple, Fair and Discretionary Administrative Law - Knight, Dean R (Victoria University of Wellington Law Review, 2008)
This article discusses the immense contribution Lord Cooke made to the development of administrative law in New Zealand. It focuses on his desire for simplicity, his pursuit of fairness and his acceptance of discretion. In particular, this article examines the different ways this tripartite set of themes manifest themselves in and throughout the orthodox tripartite grounds of judicial review in New Zealand.